Effectiveness of Preventive Therapy for Persons Exposed at Home to Drug-Resistant Tuberculosis, Karachi, Pakistan - Malik, Amyn A.; Gandhi, Neel R.; Lash, Timothy L.; Cranmer, Lisa M.; Omer, Saad B.; Ahmed, Junaid F.; Siddiqui, Sara; Amanullah, Farhana; Khan, Aamir J.; Keshavjee, Salmaan; Hussain, Hamidah; Becerra, Mercedes C. (Emerging infectious diseases, 2021)
In Karachi, Pakistan, a South Asian megacity with a high prevalence of tuberculosis (TB) and low HIV prevalence, we assessed the effectiveness of fluoroquinolone-based preventive therapy for drug-resistant (DR) TB exposure. During February 2016–March 2017, high-risk household contacts of DR TB patients began a 6-month course of preventive therapy with a fluoroquinolone-based, 2-drug regimen. We assessed effectiveness in this cohort by comparing the rate and risk for TB disease over 2 years to the rates and risks reported in the literature. Of 172 participants, TB occurred in 2 persons over 336 person-years of observation. TB disease incidence rate observed in the cohort was 6.0/1,000 person-years. The incidence rate ratio ranged from 0.29 (95% CI 0.04–1.3) to 0.50 (95% CI 0.06–2.8), with a pooled estimate of 0.35 (95% CI 0.14–0.87). Overall, fluoroquinolone-based preventive therapy for DR TB exposure reduced risk for TB disease by 65%.